MODEL PENGEMBANGAN DALAM MENINGKATKAN KUALITAS LINGKUNGAN FISIK KAWASAN SIMPANG TUJUH ULEE KARENG BANDA ACEH - Efa Maisara; Ashfa Achmad; Azmeri Azmeri (Prodi Magister Teknik Sipil Unsyiah, 2020)
The rapid area development phenomenon which is not undirected and uncontrolled as well as the rapid population growth becomes the problems related to the spatial utilization. The area requires the proper management both building and environment such as in Simpang Tujuh Ulee Kareng (STUK) Area located in Banda Aceh as economic activity center area both service and trade of Ulee Kareng Community.STUK development due to strategic location, high accessibility and activity actors improvement can impact the traffic problem and unwell informal sector activity affecting the decrease of environment quality from bio-physical and socio-economic aspects if not balanced by the area capacity improvement. This research aims to find out the difference of STUK environment quality between bio-physical and socio-economic aspects according to community and compile the model of STUK Area Development in improving urban environment quality. The advantage of the research is providing the information and input to Banda Aceh Government. The methods used are qualitative and quantitative. The questionnaires were distributed to 100 respondents in obtaining the primary data as well as FGD inviting both community and government elements.The research results that both bio-physical and socio-economic aspects highly affect environment quality decrease in which the traffic affecting 70.41% and legal aspect affecting 57.51%. The results meet ANAVA analysis resulting that the highest average difference of these two aspects is 0.52. FGD implementation results that the community highly supports the management of STUK Area using the proper area development model. The model applied is renewal method using land consolidation system.